Studi kasus : Feline lower urinary tract disease (flutd) pada kucing nobu di k and p clinic - Remigio Jordan; Ajeng Febrianix; Victor Yullius; Intan Permatasari Hermawan (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2022)
The purpose of this case study is to find out cases of urolithiasis in cats related to the type of stone or mineralization which is often the biggest cause of Feline Lower Urinary Tract Disease (FLUTD) in Surabaya in 2021. This case was characterized by the cat having difficulty defecating, decreased appetite. , urinate little by little and when palpation of the bladder feels like a big ball. In this case study, Cat Lower Urinary Tract Disease examination (FLUTD) was carried out with supporting diagnosis using urinalysis tests, microscopy tests and palpation to determine the condition of the urinary bladder (VU). After that, there is mineralization that accumulates in the bladder, which makes the bladder become large due to blockage of the urinary tract so that the bladder looks large. Interflox therapy dose of 0.1ml x /kgBB (5.20 kg) = 0.52ml given at 06.00 am, Dexa dose of 0.25 for all sizes is only given on 15-19 February 2020 given at 13.00 pm. Viamin dose 0.3 ml x / kg body weight (5.20 kg) = 1.56 ml given at 05.00 am, 13.00 pm and 17.00 pm. stamp is given at 05.00 am and 17.00 pm , Phytomenadione is given when needed.